Adding low ankle brachial index to classical risk factors improves the prediction of major cardiovascular events. The REGICOR study. Issue 2 (August 2015) - Velescu, A.; Clara, A.; Peñafiel, J.; Ramos, R.; Marti, R.; Grau, M.; Dégano, I.R.; Marrugat, J.; Elosua, R.
Abstract: Objectives: Cardiovascular risk estimation is a key element of current primary prevention strategies, despite its limited accuracy. Several biomarkers are being tested to assess their capacity to improve coronary (CHD) and cardiovascular (CVD) prediction. One of these biomarkers is ankle brachial index (ABI). The aim of this study was to assess whether the inclusion of ABI improved the predictive capacity of the Framingham-REGICOR risk function in an area of low CVD incidence. Methods: A total of 5248 individuals, aged 35–74 years, from a prospective population-based cohort study were followed up for a median 5.9 years. Baseline ABI was measured using a standardized method. All incident CHD (angina, myocardial infarction, coronary revascularization, CHD death) and CVD (also including fatal and non-fatal stroke) events were recorded. Improvements in discrimination (ΔC-statistics) and reclassification by net reclassification index (NRI) were assessed. Results: During follow-up, 111 and 64 subjects presented with a coronary or cerebrovascular event. Pathological ABI (≤0.9) was associated with increased CHD and CVD risk (HR: 2.08 and HR: 2.24, respectively; p-value < 0.001). Including ABI in the Framingham-REGICOR function improved both its discrimination and its reclassification capacity for CVD events but not for CHD events; the ΔC-statistic for CVD events was 0.007 (95% Confidence Interval: 0.001; 0.017) and the NRI was 0.029 (95% CI: 0.014–0.045; p-value < 0.001). Conclusion: Inclusion of the ABI improves the predictive capacity of the Framingham-REGICOR risk function. The study results indicate the potential value of including this simple test in cardiovascular risk stratification and support current guidelines recommendations. Highlights: Ankle brachial index (ABI) is associated with coronary and cardiovascular events. Adding ABI improves the predictive capacity of a classical risk function. This improvement is higher in the group of the population with intermediate risk. These results support the inclusion of ABI in cardiovascular risk stratification.